Selected agroclimatic characteristics of climatic regions of the Czech Republic - KOHUT, Mojmír; CHUCHMA, Filip; HORA, Petr (Contributions to Geophysics and Geodesy, 2012)
The current division of the Czech Republic into climatic regions was carried out according to basic criteria which meet the assumption  of similar conditions for growth and development of agricultural crops. Ten climatic regions in the Czech Republic were labelled with numbers 0 (VT, very hot) to 9 (CH, cold). In this paper we have utilized selected agro-climatic characteristics for these climatic regions, which were not considered in the original classification. Evaluation was performed according to the daily interval of agro- meteorological model AVISO with the use of technical series of meteorological elements of a regular network of 789 grid points (10×10 km) for the period of 1961–2010.